Transcriptome-Wide Identification of WRKY Transcription Factor and Functional Characterization of RgWRKY37 Involved in Acteoside Biosynthesis in Rehmannia glutinosa - Wang, Fengqing; Li, Xinrong; Zuo, Xin; Li, Mingming; Miao, Chunyan; Zhi, Jingyu; Li, Yajing; Yang, Xu; Liu, Xiangyang; Xie, Caixia (Frontiers in Plant Science, 2021)
WRKYs play important roles in plant metabolism, but their regulation mechanism in R. glutinosa remains elusive. In this study, 37 putative WRKY transcription factors (TFs) with complete WRKY domain from R. glutinosa transcriptome sequence data were identified. Based on their conserved domains and zinc-finger motif, the R. glutinosa WRKY TFs were divided into five groups. Structural feature analysis shows that the 37 RgWRKY proteins contain WRKYGQK/GKK domains and a C2H2/C2HC-type zinc-finger structure. To identify the function of RgWRKY members involved in acteoside biosynthesis, transcriptional profiles of 37 RgWRKYs in hairy roots under salicylic acid (SA), methyl jasmonate (MeJA) and hydrogen peroxide (H2O2) treatments were systematically established using RNA-seq analysis. Based on the correlationship between the expression levels of RgWRKY genes and acteoside content, RgWRKY7, RgWRKY23, RgWRKY34, RgWRKY35 and RgWRKY37 were suggested to be involved in acteoside biosynthesis in R. glutinosa, and RgWRKY37 was selected for gene functional research. Overexpression of RgWRKY37 increased the content of acteoside and total phenylethanoid glycosides (PhGs) in hairy roots and enhanced the transcript abundance of seven enzyme genes involved in the acteoside biosynthesis pathway. These results strongly suggest the involvement of the WRKY transcription factor in the regulation of acteoside biosynthesis.